A review of specifications for lateritic materials for low volume roads. (December 2015) - Paige-Green, P.; Pinard, M.; Netterberg, F.
Abstract: Most laterite or lateritic soils do not comply with traditional specifications for road layers. This is a particular problem when materials are required for low volume roads. However, experience with many lateritic materials has shown that they can be successfully used with specifications that are outside traditional requirements. A review of various specifications concluded that the specifications used in Brazil are probably those based on the most pertinent and detailed research. This paper discusses the wide range of specifications suggested internationally for lateritic materials and compares the properties of a number of lateritic materials successfully used in roads in various sub-Saharan countries with the Brazilian specifications suggested for interim use in southern Africa.